Collapsible properties of Q2 loess and its collapsible prediction model - Yukai FU; Guanglin LI; Tonglu LI; Ziran ZHANG; He LIU (Shuiwen dizhi gongcheng dizhi)
Long-term surface leakage caused by intermittent surface irrigation or project operation can lead to the humidification and settlement deformation of deep Q2 loess, compromising the safety of the structures. To predict the collapsible deformation properties of Q2 loess, a series of high pressure consolidation tests were performed under different water contents on Q2 loess from Jingyang of Shaanxi Province. The collapsible coefficients under different water contents were measured by using double-line method tests, and the collapsibility of Q2 loess of different water contents and pressures within high pressure range were investigated. Based on these experimental results, a pressure-dependent collapsibility coefficient model in the δs-p semi-logarithmic coordinates was proposed by using linear and Lorentz-type joint functions. Furthermore, a 3D collapsible surface model related to the pressure and water content was proposed based on the correlation analysis between model parameters and water content. The test results indicates that all collapsible coefficients in the δs-p semi-logarithmic coordinates present the trend of linear slow increase-sudden increase-peak-decrease with the increasing pressure. The boundary pressure between the slow increase stage and sudden increase stage remains unaffected by changes in water content and corresponds to the structural yield pressure of the saturated compression curve. Additionally, the peak collapsible coefficient and its corresponding pressure decreases with the increase of water content. The proposed model can accurately describe the variation of collapsibility coefficient of Q2 loess with different water contents throughout the high pressure consolidation, which is of practical significance to evaluate the collapsibility of deep and thick Q2 loess under water immersion and humidification.